2007
DOI: 10.1002/joc.1516
|View full text |Cite
|
Sign up to set email alerts
|

Time variations of the effects of circulation variability modes on European temperature and precipitation in winter

Abstract: Five modes of variability are identified in winter monthly mean 500 hPa heights over the Euro-Atlantic sector by rotated principal component analysis. Time variations of the effects of the modes on temperature and precipitation at more than 100 European stations are examined for period . Time variations are investigated by running correlations with the 15-year window. At most of the stations, the correlations with circulation patterns vary considerably in time, both for temperature and precipitation. The spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 55 publications
(57 reference statements)
0
73
1
Order By: Relevance
“…The results presented here are not in accordance with the results published by Beranová, Huth (2008). One of their conclusions was that the impact of the NAO on precipitation in Central Europe was insignificant.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results presented here are not in accordance with the results published by Beranová, Huth (2008). One of their conclusions was that the impact of the NAO on precipitation in Central Europe was insignificant.…”
Section: Discussioncontrasting
confidence: 99%
“…During the negative phase, the stormtracks move towards the Mediterranean region, where higher air temperature and precipitation totals are recorded during this phase. On the other hand, the precipitation totals are below-normal in Scandinavia and in the British Isles (Hurrell, 1995;Hurrell, 2001;Barry, Chorley, 2003;Doležalová, 2007;Beranová, Huth, 2008). The temperatures in Central Europe correlate positively with the NAO phases, but there is a more complicated relation between the NAO and precipitation totals (see below).…”
Section: The Concept Of the North Atlantic Oscillationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case for the southern basins, where significant regulation capacity has been generated in the last 60 yr (Arroyo-Ilera, 2007). The intensive regulation of river systems in the IP is reflected in an increase in the number of major reservoirs constructed during the 20th century (from 58 in 1900 to 1195 in 2000), reaching a total storage capacity of 56 500 hm 3 (Berga-Casafont, 2003). This capacity is approximately equal to the mean annual streamflow of the 8 major rivers of the IP (55 850 hm 3 ).…”
Section: Study Areamentioning
confidence: 99%
“…Within the Iberian Peninsula (hereafter IP) the influence of the NAO on river discharges has been analyzed in studies of various basins (López-Moreno et al, 2007;Trigo et al, 2004;Morán-Tejeda et al, 2011), where reasonably high correlations have been found between the NAO and streamflows, particularly in winter. Nevertheless, there remain gaps in understanding of the nature of this relationship and its spatio-temporal variability, as recent studies (Beranová and Huth, 2008;) have shown a non-stationary influence of the NAO on the climate in Europe. Moreover, no studies have considered the IP as a whole, which is necessary to gain an understanding of the spatio-temporal dynamics of the relationship.…”
Section: Introductionmentioning
confidence: 99%